Kepahlawanan dalam Lagu-Lagu Perjuangan Nahdlatul Wathan Karya Hamzanwadi - Karmilawati Karmilawati (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2018)
This study aims to describe the forms of the heroes' characteristics and describe the heroic messages contained in the struggle songs of Nahdlatul Wathan (NW) by T.G.K.H. Muhammad Zainuddin Abdul Madjid (also known as Hamzanwadi). This research method is descriptive qualitative with content analysis technique which focuses research on the latent content of song texts as research data. This technique is done by reading, recording, and coding, which determines the themes of each form and the heroic message found in each song. The results of this study indicate that the form of heroism contained in the songs of struggle is the attitude of love of knowledge which is realized by diligently demanding knowledge, as well as the attitude of love for religion and nation which is realized through willingness to fight. The heroic message found is a call as well as an invitation to the ummah to have a noble character that is based on the knowledge of the realization of good relations between humans and God, humans and humans, and humans with nature.